1978
DOI: 10.1366/000370278774331341
|View full text |Cite
|
Sign up to set email alerts
|

Raman Microprobe Characterization of Residual Carbonaceous Material Associated with Urban Airborne Particulates

Abstract: Analyses of individual urban airborne particulates were conducted in the Raman microprobe. In addition to the spectral features characteristic of the particle, two features at ∼1350 and ∼1600 cm−1 have been observed. The appearance of these bands is found to vary a function of the laser irradiance. By modeling experiments, it is demonstrated that these two bands can be explained by the presence of carbon in a form analogous to polycrystalline graphite. In air particulates the source of the carbon can be either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The number of spectra measurable in a short time period by RT Raman instruments is also limited because some particles can be charred or physically modified by higher laser intensities (e.g., > 1 mW mm 2 ) (e.g., Blaha, Rosasco, and Etz 1978;Lai et al 2016). Thus, there is a complex tradeoff between laser intensity (scales positively with potential for burning), laser wavelength (Raman intensity scales as 1/k 4 , but also fluorescence is generally stronger at shorter excitation wavelengths), and imaging/photobleaching time versus sample rate.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…The number of spectra measurable in a short time period by RT Raman instruments is also limited because some particles can be charred or physically modified by higher laser intensities (e.g., > 1 mW mm 2 ) (e.g., Blaha, Rosasco, and Etz 1978;Lai et al 2016). Thus, there is a complex tradeoff between laser intensity (scales positively with potential for burning), laser wavelength (Raman intensity scales as 1/k 4 , but also fluorescence is generally stronger at shorter excitation wavelengths), and imaging/photobleaching time versus sample rate.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…For a positively charged particle, the potenthe volume of the particle (20,21), the signal decreases tials on the ring (R), upper (U) endcap, and lower (L) dramatically with size. Blaha et al (22) reported data for fine encap are described by particles (200-500 nm) attached to substrates, but Raman spectra from suspended or flowing particles have only been V R Å V ac cos vt, [3] reported for particles down to 1-2 mm in diameter (23)(24)(25). Raman spectroscopy is truly an in situ method.…”
Section: Introductionmentioning
confidence: 99%
“…A complementary technique useful for this field of study is the Raman microspectroscopy, employed for the characterization of graphitic materials (Sadezky et al 2005) and soot particles (Blaha et al 1978;Sze et al 2001;Ivleva et al 2007a), for the reason that the honeycomb carbon structure produces a typical vibrational spectrum that allows to recognizing crystalline graphite, ordered, disordered and amorphous carbon, as well as organic matter. Using Raman micro-spectroscopy it is possible to analyze single particles aggregates (Batonneau et al 2006;Ivleva et al 2007b;Stefaniak et al 2009), collecting a spectrum from each one, and then performing a statistical analysis.…”
mentioning
confidence: 99%